Teaching History and Geography in an Amazon riverside community in Brazil - Thaís Gonçalves Silva; Germana Ponce de Leon Ramirez (Revista Brasileira de Educação do Campo, 2022)
The traditional communities in Brazil demonstrate how rich Brazilian multiculturalism is. For example, in this Amazon context are the inhabitants of the floodplain, which are called Riverines. It is questioned whether the municipal school of Barreirinha located on the banks of the Massauari River, in Amazonas, contemplates this specific riverside knowledge. The general objective is to analyze the pedagogical practices in the teaching of History and Geography in the school space of a Riverine community in the Lower Amazon, in the municipality of Barreirinha. Based on the primary data through open interviews with teachers and managers, it is identified that in the teaching practices, they don’t feel sufficiently prepared to deal with the specificities of a traditional Community – History teaching needs to be contextualized, as the perception of time and reality is different. The need for the student to know their own history and to place themselves within a larger national or global plan. It’s concluded that for the learning process to occur among riverside students, a change in the training of teachers is necessary in order to awaken in future teachers the importance of identifying cultural specificities in traditional communities, thus enabling meaningful teaching for students.